Ist1 regulates ESCRT-III assembly and function during multivesicular endosome biogenesis in Caenorhabditis elegans embryos - E. B. Frankel (Nature Portfolio, 2017)
During the oocyte-to-embryo transition in C. elegans, multivesicular endosomes (MVEs) are formed rapidly. Using live imaging and electron microscopy, the authors here show that the ESCRT-III subunit Ist1 is required for normal MVE biogenesis in the early C. elegans embryo.